Re-articulating forest politics through “rights to forest” and “rights of forest” - Meriläinen, Eija; Lehtinen, Ari (Geoforum, 2022)
Forests, and the politics around them, are posited both as a cause of and solution to the contemporary ecological crisis. This paper explores how rights to forest and rights of forest conceptualisations can re-articulate, and potentially challenge, the problematic dominance of capitalist forest politics in Northern Finland and beyond. Conceptually, the paper combines the debates on rights-to-nature and rights-of-nature. Rights-to-nature is concerned with how people can access and use nature to support their lives. Rights-of-nature, meanwhile, highlights the nature's intrinsic value and the rights of indigenous peoples. Combining the two perspectives might allow imagining politics of nature that is both ecologically and socially just. Empirically, the paper studies forest politics in Tornio River valley in Northern Finland through an ethnographic case study. The rights-to-nature conceptualisation associates locally with the existing use rights and ownership rights. Rights-to-nature may guarantee access to a forest, but it does not guarantee its existence. Rights-of-nature, meanwhile, associates with strong conservation, nature's power, and indigenous land rights. However, also the rights-of-nature conceptualisation is unlikely to challenge the gradual degradation of most Northern forests, as these “boring” forests lack both recognised human stewardship and intrinsic value. Thus, in the study area the rights conceptualisations do not decisively challenge the existing forest politics, even if the framings can acquire a more radical content. Overall, this paper shows that transnational rights discourses and conceptualisations entangle with local common senses. Factoring in the local understandings is essential for re-articulating politics of nature that could receive broad local support. Peer reviewed